The Impact of Asian Games 2018 on Indonesian Economy - Epson Prasetyo; I Gede Agus Ariutama; Acwin Hendra Saputra (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2021)
Organizing the 18th Asian Games 2018 in Indonesia, specifically in DKI Jakarta, South Sumatra, West Java, and Banten spent a large amount of state and regional budget (APBN and APBD), which was more than Rp10 trillion in the 2018 fiscal year. The government policy to host the mega event and expend a large amount of budget in terms of government consumption and investment was expected to have an impact on the Indonesian economy, both directly and indirectly. Thus, this study aims to identify the impact of government expenditure using the 2010 Input-Output table issued and updated by the Central Bureau of Statistics in July 2019 with 17 sectors. The study found that the multiplier effect on the economy is greater than government expenditure with the manufacturing sector being the most affected sector by government spending with a value of six point seven trillion rupiah. In addition to the multiplier effect, this study also calculates the estimated Value Added Tax of government spending. The result of the estimated Value Added Tax potential is one point sixty one trillion rupiah. It can be concluded that the Asian Games 2018 brought positive impact on economy and government revenue in the form of taxation.